Stock Separation of Tenualosa Ilisha in Bangladesh Waters Using Parasites as Biological Tag - Bhuiyan, Md Aminul Islam; Jhinu, Zannatun Nahar (Journal of the Asiatic Society of Bangladesh, Science, 2020)
Fourteen species under eleven genus of endohelminths were identified from alimentary canal and associated organs of host, only two of them had satisfied the criteria of being as biological tag. These are one species of cestode parasite named Ilisha parthenogenetica and two acanthocephalan parasite species named Acanthocentis indica and Acanthocentis hilsai, which are in together termed as Acanthosentis spp. The presence of these parasites in all the habitats indicates host’s anadromous nature as well as higher prevalence of these tag parasites at respective sites and the trend of prevalence of infection in size class of host fish reinforced the belief that T. ilisha population in Bangladesh are largely anadromous in nature that cannot currently be divided into a group of discrete stocks and as a whole, a single stock of T. ilisha migrates from the sea to the rivers through the estuaries and vice versa. J. Asiat. Soc. Bangladesh, Sci. 46(1): 61-70, June 2020